Reproductive performance, metabolic and hormonal profiles of Santa Inês ewes in winter and summer under tropical conditions - Balaro, Mario Felipe Alvarez; Brandão, Felipe Zandonadi; Peneiras, Anna Beatriz Veltri; Oba, Eunice; da Fonseca, Jeferson Ferreira; Almosny, Nádia Regina Pereira; da Cruz Cardoso, Elyzabeth (Springer Nature, 2015)
The study aimed to evaluate the reproductive, metabolic and hormonal profiles of Santa Inês ewes during winter and summer in the tropical climate of Rio de Janeiro State, Brazil. The ewes (n = 16) were prepared for induction of synchronised oestrus with a short-term hormonal treatment, and follicular dynamics were assessed with ultrasonography. Blood samples for biochemical and hormonal analyses were collected on days zero, six and eight of the protocol at 7, 13 and 19 h. Reproductive behaviour did not differ (P > 0.05) between seasons. Based on ultrasonography data, the ovulation rate was 100 % in summer and 81.3 % in winter. Most of the ewes showed double ovulation in summer, and the diameter of the largest and second largest follicles differed (P < 0.05) between seasons. Among the biochemical parameters, plasma glucose, plasma urea and serum albumin differed (P < 0.05) between the study periods. Regarding the hormonal profile, higher serum triiodothyronine, thyroxine and prolactin concentrations (P < 0.05) were observed in summer. The average progesterone concentrations demonstrated low reproductive seasonality. In conclusion, the reproductive performance of the ewes was superior in summer, and higher levels of plasma glucose and serum albumin during this season may have played a role in the observed ovulation rates. The higher levels of serum prolactin and serum thyroxine in summer demonstrated that these compounds were not involved in the regulatory mechanisms underlying the onset of anoestrus in these Santa Inês ewes under tropical conditions.
Keywords: Biochemical; Ewe; Hormones; Oestrous; Seasonality; Tropical